The protégé. [videorecording (DVD)] - Campbell, Martin; Q., Maggie (Maggie Quigley), 1979-; Jackson, Samuel L.; Keaton, Michael, 1951- (Lionsgate, 2021)
Rescued as a child by an assassin, a girl grows up to become the best contract killer, and when the man who rescued her and taught her everything she knows is murdered, she sets off to avenge his death.